Noncovalently Immobilized Glucose Oxidase/Horseradish Peroxidase Cascade on Polyamide Supports for Eco-Friendly Polyaniline Synthesis - Nadya V. Dencheva; Joana F. Braz; Sofia A. Guimarães; Zlatan Z. Denchev (Molecules)
This study discloses the noncovalent immobilization of a bienzyme cascade composed of glucose oxidase (GOx) and horseradish peroxidase (HRP) onto magnetically responsive polyamide microparticles (PA MPs). Porous PA6, PA4, and PA12 MPs containing iron fillers were synthesized via activated anionic ring-opening polymerization in suspension, alongside neat PA6 MPs used as a reference. Four hybrid catalytic systems (GOx/HRP@PA) were prepared through sequential adsorption of HRP and GOx onto the various PA MP supports. The initial morphologies of the supports and the hybrid biocatalysts were characterized by SEM, followed by evaluation of the catalytic performance using a two-step glucose oxidation cascade process. Among all systems, the GOx/HRP@PA4-Fe complex exhibited the highest activity, being approximately 1.5 times greater than the native enzyme dyad, followed by the PA6-supported system with slightly inferior performance. All systems obeyed Michaelis–Menten kinetics, with the immobilized cascades displaying higher Kₘ and Vₘₐₓ values than the non-immobilized enzyme pair while maintaining comparable catalytic efficiencies, CE (CE = kcat/Kₘ). Subsequently, the immobilized and native enzyme systems were employed for the polymerization of aniline. According to UV–VIS, complete monomer conversion was achieved within 24 h for selected catalysts, and FTIR analysis confirmed the formation of polyaniline in the emeraldine base form without the use of template molecules. These findings highlight the potential of Fe-containing polyamide microparticles as efficient supports for the sustainable, enzyme-mediated synthesis of intrinsically conductive aromatic polymers.